Habitat Characteristics of Long-Tailed Macaque (Macaca fascicularis Raffles, 1821) in Kucur Resort at Alas Purwo National Park - Siddiq, Arif Mohammad; Wati, Dewi Erna; Sulistiyowati, Hari; Wimbaningrum, Retno; Setiawan, Rendy; Supriadi, Dudun (Universitas Jember, 2022)
The Long-Tailed Macaque (LTM) (Macaca fascicularis Raffles, 1821) is a member of the Cercopithecidae which is included in the Vulnerable status. Information on the habitat characteristics of these species is needed to support in-situ conservation efforts. This study aims to determine the habitat characteristics of LTM in Kucur Resort at Alas Purwo National Park (APNP) based on the forest strata occupied by the LTM, Normalizes Difference Vegetation Index (NDVI), and river distance. The research procedure begins with a preliminary survey to determine the six lines of observation. The data used are primary data (LTM encounter points, forest strata they occupy, and data on tree species where they meet) and secondary data (NDVI variables and river distance). Both data were analyzed using a Geographic Information System (GIS) approach. The results showed that the LTM at Resort Kucur TNAP was found in four different groups. The results of data analysis show that the habitat characteristics of the LTM in Kucur Resort based on the forest strata it occupies are at a tree height level of 0-30 meters (strata E-B) which has branches, canopies, and produces young leaves and fruits. Furthermore, the LTM habitat has vegetation characteristics with medium density and cover which has an NDVI value of 0.3-0.5. This indicates the character of this habitat is used as a place to rest, socialize, and avoid from predators. Based on the distance of the river, the habitat characteristics are the location which is quite far from the river, which is > 300 meters. Based on the data on the habitat characteristics of LTM, it shows that Kucur Resort provides a fairly good habitat for the LTM.